Preparation method of mulberry silk elastic twisted fabric

CN122918759APending Publication Date: 2026-10-16JIANGXI MISIMI WEAVING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611182490.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

S1:制备抗菌粘胶纤维

Benefits of technology

1、本发明采用水解聚马来酸酐与油酸分步处理粘胶纤维,通过两步独立的反应,在纤维内部与表面分别构建功能层,实现单一处理无法达到的协同增效。第一步,水解聚马来酸酐作为多元羧酸,在高温和次亚磷酸钠催化下,与纤维素分子链上的羟基发生酯化交联反应,在复合处理粘胶纤维内部搭建稳固的骨架,显著提升复合处理粘胶纤维的断裂强度;并且通过水解马来酸酐的改性,改变了粘胶纤维的表面性能,降低了粘胶纤维表面的湿膨胀率,使其具备更好的弹性回复率和抗皱性能,第二步,第一步中经过水解聚马来酸酐的改性,粘胶纤维表面活性增强,油酸通过物理吸附和化学键合在高活性的纤维表面形成润滑膜,在其长链烷基有效降低了纤维间的摩擦系数,从而进一步提高复合处理粘胶纤维的弹性,并通过降低摩擦系数,减少内部消耗,从而提高物理断裂强度,二者协同配合,在纤维的内部性质和纤维间的摩擦系数上共同进行改善,大幅提升复合处理粘胶纤维的弹性和物理强度。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122918759A_ABST
    Figure CN122918759A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of mulberry silk blended fabric, in particular to a preparation method of mulberry silk elastic twisted silk fabric. The method comprises the following steps: preparing antibacterial viscose fiber, preparing composite treated viscose fiber, preparing epoxy soybean oil-tea seed oil modified fiber, and preparing mulberry silk elastic twisted silk fabric. The method adopts hydrolyzed polymaleic anhydride and oleic acid to treat viscose fiber in steps, constructs functional layers in the interior and surface of the fiber through two-step independent reactions, realizes synergistic effect that cannot be achieved by single treatment, improves the elasticity of the composite treated viscose fiber by improving the internal properties of the fiber and the friction coefficient between the fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of mulberry silk blended fabric technology, specifically to a method for preparing mulberry silk elastic gypsum fabric. Background Technology

[0002] Jiaoluo is one of my country's traditional silk varieties. It employs a twisted warp weave technique, where the warp yarns twist together and interweave with the weft yarns to form a fabric with a regularly spaced perforation structure. Jiaoluo fabric is lightweight, breathable, and has clearly defined perforations, possessing both excellent drape and a unique textural beauty. It has been a representative of high-end silk fabrics since ancient times. Traditionally, jiaoluo fabric is typically made from a blend of mulberry silk and other fibers. Mulberry silk gives the fabric an excellent luster and feel, while other fibers provide good moisture absorption, breathability, and softness.

[0003] Fibers used in blends with silk, such as viscose fiber, are a major type of regenerated cellulose fiber. They possess advantages such as good moisture absorption and a soft hand feel. However, during the production process, the cellulose macromolecular chains of viscose fiber undergo severe degradation, resulting in a degree of polymerization far lower than that of natural cellulose fibers like cotton and linen. Shorter molecular chains lead to weaker intermolecular forces, making them more prone to relative slippage under external forces. This results in inherent defects in viscose fiber, such as lower tensile strength and insufficient elastic recovery. Therefore, it is necessary to reinforce and modify viscose fiber, for example, by adding functional fillers to the spinning solution. Current technologies primarily focus on improving the antibacterial properties of the spinning solution, such as by adding antibacterial silver ions before spinning. However, less attention is paid to modifying the fiber surface, and even less attention is paid to improving the strength and elasticity of the fiber itself. Furthermore, improving the surface properties of fibers, such as elasticity or smoothness, can also ensure the smoothness and efficiency of fiber spinning. Therefore, this invention provides a method for preparing mulberry silk elastic gypsum fabric, which, while ensuring the antibacterial and antimicrobial properties of the fabric, also provides superior physical strength and elasticity, and enables the fibers in the fabric to have better spinning smoothness and efficiency, thus solving the problems existing in the prior art. Summary of the Invention

[0004] In view of the shortcomings of the existing technology, the purpose of this invention is to provide a method for preparing mulberry silk elastic gypsum fabric.

[0005] A method for preparing mulberry silk elastic gypsum fabric includes the following steps: S1: Preparation of antibacterial viscose fibers Viscose fiber spinning solution, nano-paleite fiber and nano-silver colloidal aqueous solution are mixed and stirred to obtain a mixture. The mixture is degassed and filtered, metered by a spinning metering pump and ejected through a spinneret. The spinneret enters a coagulation bath for regeneration and molding to obtain fiber bundles. The fiber bundles are then subjected to two-bath stretching, washing, desulfurization, oiling and winding to obtain antibacterial viscose fiber. S2: Preparation of composite treated viscose fibers Hydrolyzed polymaleic anhydride and sodium hypophosphite were dissolved in deionized water, stirred evenly, and the pH was adjusted to obtain a pretreatment solution. Antibacterial viscose fibers were completely immersed in the pretreatment solution to ensure full penetration. The antibacterial viscose fibers were then removed, extruded using a rolling mill, pre-dried, and then heat-treated, washed, and dried to constant weight to obtain pretreated fibers. Oleic acid and Tween-80 were mixed and slowly added to warm water with stirring to obtain an oleic acid emulsion. The pretreated fibers were immersed in the oleic acid emulsion and treated in a water bath. The pretreated fibers were then removed, washed with deionized water, and dried to constant weight to obtain composite treated viscose fibers. S3: Preparation of epoxidized soybean oil-tea seed oil modified fiber Epoxidized soybean oil and camellia seed oil were mixed evenly, and then Tween-80 and OP-10 were added and stirred to obtain a mixed oil. Deionized water was added dropwise to the mixed oil while stirring until a milky white uniform emulsion was formed. The emulsion was then ultrasonically treated to obtain a mixed emulsion. The mixed emulsion was added to deionized water and stirred evenly to obtain a mixed oil treatment solution. The composite-treated viscose fiber was completely immersed in the mixed oil treatment solution and treated in a water bath. The composite-treated viscose fiber was then removed, extruded using a rolling mill, pre-dried and treated in an oven, and finally washed with deionized water and dried to constant weight to obtain epoxidized soybean oil-camellia seed oil modified fiber. S4: Preparation of mulberry silk elastic gneiss fabric Twisted mulberry silk was used as warp yarn, and epoxidized soybean oil-tea seed oil modified fiber was used as weft yarn. The warp density was 330 threads / 10cm and the weft density was 260 threads / 10cm. The fabric was woven into a four-warp gauze fabric using a rapier loom to obtain mulberry silk elastic gauze fabric.

[0006] Further, step S1, which involves preparing antibacterial viscose fibers, specifically includes the following steps: 200-210 parts by weight of viscose fiber spinning solution, 20-25 parts by weight of nano-paflictrine fiber, and 60 parts by weight of nano-silver colloidal aqueous solution are mixed and stirred at 200-300 r / min for 30-40 minutes, controlling the temperature of the solution after mixing at 30℃ to obtain a mixture. The mixture is then degassed and filtered, and metered through a spinning metering pump and ejected through a spinneret. The spinneret enters a coagulation bath for regeneration and shaping to obtain fiber bundles. The fiber is drawn through a two-bath process, followed by washing, desulfurization, washing, oiling, and winding to obtain antibacterial viscose fiber. The coagulation bath consists of 102.0-105.0 g / L sulfuric acid, 330.0-360.0 g / L sodium sulfate, and 8.5-9.5 g / L zinc sulfate. The temperature of the coagulation bath is 46-48℃. The two-bath drawing bath consists of 45.0-65.0 g / L sulfuric acid at a temperature of 75-80℃ and a spinning speed of 35 m / min.

[0007] Further, step S2 involves preparing composite-treated viscose fibers, specifically including the following steps: Dissolve 0.16-0.18 parts by weight of hydrolyzed polymaleic anhydride and 0.06-0.08 parts by weight of sodium hypophosphite in 60 parts by weight of deionized water, stir well, and adjust the pH to 3-4 with sodium bicarbonate to obtain the pretreated solution. Immerse 2-2.5 parts by weight of antibacterial viscose fiber completely in the above pretreatment solution and soak at room temperature (22-24℃) for 30-35 minutes to allow the pretreatment solution to fully penetrate. Then, remove the antibacterial viscose fiber, squeeze it with a rolling mill, and then pre-dry it in an oven at 80-90℃ for 5 minutes. Treat the pre-dried fiber in an oven at 180-190℃ for 3-5 minutes. Wash the product thoroughly with deionized water 3 times and finally dry it at 50-60℃ to constant weight to obtain the pretreated fiber. Mix 0.04-0.06 parts by weight of oleic acid with 0.02 parts by weight of Tween-80, and slowly add the mixture to 60 parts by weight of warm water at 50-55°C while stirring. Stir at 800-900 r / min for 10-15 min to obtain an oleic acid emulsion. Immerse 2-3 parts by weight of the pretreated fiber in the above oleic acid emulsion and treat it in a water bath at 50-55°C for 30-35 minutes. Then take out the pretreated fiber, wash it with deionized water 2-3 times, and dry it at 50-60°C to constant weight to obtain composite treated viscose fiber.

[0008] Further, step S3, preparing the nanoemulsion, specifically includes the following steps: Mix 3-5 parts by weight of epoxidized soybean oil and 7-8 parts by weight of tea seed oil at a speed of 200-300 r / min until homogeneous. Then add 2-3 parts by weight of Tween-80 and 1-2 parts by weight of OP-10, and stir at a speed of 200-300 r / min until fully dissolved to obtain the mixed oil. While stirring at 1200-2000 r / min, add 25-35 parts by weight of deionized water dropwise to the mixed oil until a milky white homogeneous emulsion is formed. Sonicate for 5-10 min to obtain the mixed emulsion. Add 0.4-0.6 parts by weight of the mixed emulsion to 60 parts by weight of deionized water, stir evenly, and adjust the pH to 6-7 to obtain the mixed oil treatment solution. Two to three parts by weight of composite-treated viscose fiber are completely immersed in the mixed oil treatment solution and treated in a water bath at 40-60℃ for 30-60 minutes. The composite-treated viscose fiber is then removed, extruded using a rolling mill, and the liquid content is controlled at 80-100%. It is then pre-dried in an oven at 80-90℃ for 5-10 minutes, treated in an oven at 120-150℃ for 3-5 minutes, and finally washed 2-3 times with deionized water to remove unbound mixed oil treatment solution from the surface. Finally, it is dried at 60℃ to constant weight to obtain epoxidized soybean oil-tea seed oil modified fiber.

[0009] Furthermore, the preparation of the viscose fiber spinning solution in step S1 is specifically as follows: Wood pulp is soaked in a sodium hydroxide solution with a concentration of 18-20% and treated at 18-25°C for 1-2 hours. The sodium hydroxide solution is then removed by pressing. The product is then pulverized for 5-10 minutes until it is transformed into a loose flocculent body to obtain alkali cellulose. Alkali cellulose is placed in air with an oxygen concentration of 60% for 20-30 minutes to obtain aged cellulose; 10-12 parts by weight of aged cellulose are mixed with 3-5 parts by weight of carbon disulfide and reacted for 5-10 minutes to obtain cellulose carbamate. The cellulose carbamate is dissolved in a 4-6% sodium hydroxide solution to form a viscous spinning solution to obtain viscose. The viscose is placed at 30-34℃ for 22-28 hours for curing, while being filtered and degassed to obtain viscose fiber spinning solution.

[0010] Furthermore, the ratio of wood pulp to sodium hydroxide solution is 1g:(10-15)mL.

[0011] Furthermore, the ratio of cellulose carbamate to sodium hydroxide solution is 1 g: (6-10) mL.

[0012] Furthermore, the colloidal aqueous solution of nano-silver specifically contains 0.1-0.15 wt% nano-silver particles with a particle size of less than 100 nm, and 0.5-2.0 wt% amino acids are added.

[0013] Furthermore, the power of the ultrasonic treatment is 20W.

[0014] The present invention has the following advantages: 1. This invention uses hydrolyzed polymaleic anhydride and oleic acid to process viscose fibers in two steps. Through two independent reactions, functional layers are constructed inside and on the surface of the fiber, achieving synergistic effects that cannot be achieved by a single treatment. The first step involves hydrolyzing polymaleic anhydride, a polycarboxylic acid, which undergoes esterification and cross-linking with hydroxyl groups on the cellulose molecular chain under high temperature and sodium hypophosphite catalysis. This builds a stable framework within the composite-treated viscose fiber, significantly improving its tensile strength. Furthermore, the modification by hydrolyzed maleic anhydride alters the surface properties of the viscose fiber, reducing its surface wet swelling rate and resulting in better elastic recovery and wrinkle resistance. The second step, following the modification by hydrolyzed maleic anhydride in the first step, enhances the surface activity of the viscose fiber. Oleic acid forms a lubricating film on the highly active fiber surface through physical adsorption and chemical bonding. Its long-chain alkyl groups effectively reduce the coefficient of friction between fibers, further improving the elasticity of the composite-treated viscose fiber. By reducing the coefficient of friction, internal consumption is reduced, thereby increasing the physical tensile strength. These two steps work synergistically to improve both the internal properties of the fiber and the coefficient of friction between fibers, significantly enhancing the elasticity and physical strength of the composite-treated viscose fiber.

[0015] 2. This invention achieves composite functional modification of viscose fibers by mixing epoxidized soybean oil and tea seed oil. First, under heat treatment conditions, the active epoxy groups on the epoxidized soybean oil molecular chain undergo ring-opening esterification with the hydroxyl groups on the viscose fiber molecular chain to form a stable covalent bond. At the same time, because the epoxidized soybean oil molecules contain multiple epoxy groups, they can react with multiple fiber molecular chains to build a cross-linked network structure on the fiber surface and in the shallow layer. Subsequently, the active substances such as tea polyphenols and camelliasides rich in camellia seed oil are firmly anchored to the fiber through physical adsorption and synergistic interpenetration with the cross-linking network, thereby endowing the fiber with antibacterial added value. Moreover, this synergistic interpenetration with the cross-linking network effectively solves the problem of camellia oil being easily lost and washed away. Compared with directly adding camellia seed oil to viscose solution for blending, the epoxidized soybean oil of this invention acts as both a cross-linking enhancer for the fiber and a fixative for the active ingredients of camellia seed oil. Through post-treatment, it achieves a synergistic unity of structural enhancement and functional endowment for the formed viscose fiber, improving the physical strength of the epoxidized soybean oil-camellia seed oil modified fiber while endowing it with long-lasting antibacterial function.

[0016] 3. This invention improves the physical strength of fibers by introducing cellulose carbamate, utilizing its inherent physical strength as a spinning solution. Furthermore, combining nano-pachymanite fibers with cellulose carbamate through physical blending creates a synergistic network possessing both rigidity and flexibility, simultaneously enhancing the physical function and surface smoothness of antibacterial viscose fibers. Utilizing the nanoscale porous structure of nano-pachymanite, it is uniformly dispersed as a rigid nanofiller in the cellulose carbamate spinning solution. Its fibrous crystals can penetrate and anchor between the macromolecular chains of cellulose carbamate, forming a network structure similar to physical cross-linking points. This effectively transfers stress and controls the coefficient of friction to a suitable level, thereby improving both the surface smoothness and physical strength of the fibers, resulting in better spinning smoothness and efficiency for the antibacterial viscose fibers. Attached Figure Description

[0017] Figure 1 This is a flowchart illustrating the preparation method of the mulberry silk elastic gauze fabric of the present invention. Detailed Implementation

[0018] To enable those skilled in the art to better understand the technical solutions of this invention, the technical solutions of this invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of this invention.

[0019] Example 1: A method for preparing mulberry silk elastic gypsum fabric, such as Figure 1 As shown, it includes the following steps: S1: Preparation of antibacterial viscose fibers Wood pulp was soaked in a 20% sodium hydroxide solution with a pulp-to-solid ratio of 1g:12mL. The mixture was treated at 18°C ​​for 2 hours, the sodium hydroxide solution was removed by pressing, and the product was then pulverized for 5 minutes until it was transformed into a loose flocculent body to obtain alkali cellulose. Alkali cellulose is placed in air with an oxygen concentration of 60% for 30 minutes to obtain aged cellulose; 12 parts by weight of aged cellulose and 4 parts by weight of carbon disulfide were mixed and reacted for 5 minutes to obtain cellulose carbamate. The cellulose carbamate was dissolved in a 6% sodium hydroxide solution with a material-to-liquid ratio of 1g:10mL to form a viscous spinning solution, which yielded viscose. The viscose was placed at 30°C for 24 hours to mature, while being filtered and degassed to obtain viscose fiber spinning solution.

[0020] 205 parts by weight of viscose fiber spinning solution, 20 parts by weight of nano-paspalum fiber, and 60 parts by weight of nano-silver colloidal aqueous solution were mixed. The nano-silver colloidal aqueous solution specifically contained 0.12 wt% nano-silver particles with a particle size of less than 100 nm, and 2.0 wt% amino acids were added. The mixture was stirred at 300 r / min for 30 minutes, and the temperature of the mixed solution was controlled at 30℃ to obtain a mixed solution. The mixed solution was degassed and filtered, and then passed through a spinning metering pump. The fiber is metered and ejected from the spinneret. The fine filaments enter the coagulation bath for regeneration and molding to obtain fiber bundles. The fiber bundles undergo two-bath drawing, washing, desulfurization, washing, oiling, and winding to obtain antibacterial viscose fiber. The composition of the coagulation bath is: sulfuric acid 102.0 g / L, sodium sulfate 360.0 g / L, and zinc sulfate 8.5 g / L; the temperature of the coagulation bath is 48℃; the bath solution for the second-bath drawing is sulfuric acid 65.0 g / L, the temperature is 75℃, and the spinning speed is 35 m / min.

[0021] S2: Preparation of composite treated viscose fibers Dissolve 0.17 parts by weight of hydrolyzed polymaleic anhydride and 0.08 parts by weight of sodium hypophosphite in 60 parts by weight of deionized water, stir well, and adjust the pH to 3-4 with sodium bicarbonate to obtain the pretreated solution. 2.5 parts by weight of antibacterial viscose fiber were completely immersed in the above pretreatment solution and soaked at room temperature of 22°C for 35 minutes to allow the pretreatment solution to fully penetrate. Then, the antibacterial viscose fiber was taken out, squeezed with a rolling mill, and then pre-dried in an oven at 80°C for 5 minutes. The pre-dried fiber was then treated in an oven at 190°C for 3 minutes. The product was thoroughly washed three times with deionized water and finally dried at 60°C to constant weight to obtain the pretreated fiber. Mix 0.06 parts by weight of oleic acid with 0.02 parts by weight of Tween-80, and slowly add the mixture to 60 parts by weight of warm water at 55°C while stirring. Stir at 800 r / min for 15 min to obtain an oleic acid emulsion. Three parts by weight of pretreated fiber were immersed in the above oleic acid emulsion and treated in a water bath at 55°C for 30 minutes. Then the pretreated fiber was taken out and washed twice with deionized water and dried at 60°C to constant weight to obtain composite treated viscose fiber.

[0022] S3: Preparation of epoxidized soybean oil-tea seed oil modified fiber Mix 4 parts by weight of epoxidized soybean oil and 7 parts by weight of tea seed oil at a speed of 200 r / min until homogeneous. Then add 2 parts by weight of Tween-80 and 1 part by weight of OP-10, and stir at a speed of 200 r / min until fully dissolved to obtain a mixed oil. Under stirring at 1500 r / min, 35 parts by mass of deionized water were added dropwise to the mixed oil until a milky white uniform emulsion was formed. The mixture was then ultrasonically treated at 20W for 5 minutes to obtain a mixed emulsion. 0.6 parts by mass of the mixed emulsion were added to 60 parts by mass of deionized water, stirred evenly, and the pH was adjusted to 6 to obtain the mixed oil treatment solution. Three parts by weight of composite-treated viscose fiber were completely immersed in the mixed oil treatment solution and treated in a 40°C water bath for 60 minutes. The composite-treated viscose fiber was then removed, extruded using a rolling mill, and the liquid content was controlled at 80%. It was pre-dried in a 90°C oven for 5 minutes, treated in a 150°C oven for 3 minutes, and finally washed twice with deionized water to remove unbound mixed oil treatment solution from the surface. Finally, it was dried at 60°C to constant weight to obtain epoxidized soybean oil-tea seed oil modified fiber.

[0023] S4: Preparation of mulberry silk elastic gneiss fabric Twisted mulberry silk was used as warp yarn, and epoxidized soybean oil-tea seed oil modified fiber was used as weft yarn. The warp density was 330 threads / 10cm and the weft density was 260 threads / 10cm. The fabric was woven into a four-warp gauze fabric using a rapier loom to obtain mulberry silk elastic gauze fabric.

[0024] Example 2: A method for preparing mulberry silk elastic gypsum fabric, such as Figure 1 As shown, it includes the following steps: S1: Preparation of antibacterial viscose fibers Wood pulp was soaked in an 18% sodium hydroxide solution at a ratio of 1g to 15mL and treated at 25°C for 1.5 hours. The sodium hydroxide solution was then removed by pressing, and the product was pulverized for 8 minutes until it was transformed into a loose flocculent mass to obtain alkali cellulose. Alkali cellulose is placed in air with an oxygen concentration of 60% for 20 minutes to obtain aged cellulose; Ten parts by weight of aged cellulose and three parts by weight of carbon disulfide were mixed and reacted for 8 minutes to obtain cellulose carbamate. The cellulose carbamate was dissolved in a 4% sodium hydroxide solution with a material-to-liquid ratio of 1g:8mL to form a viscous spinning solution, which yielded viscose. The viscose was placed at 32°C for 28 hours to mature, while being filtered and degassed to obtain a viscose fiber spinning solution.

[0025] 210 parts by weight of viscose fiber spinning solution, 22 parts by weight of nano-paspalum fiber, and 60 parts by weight of nano-silver colloidal aqueous solution were mixed. The nano-silver colloidal aqueous solution specifically contained 0.1 wt% nano-silver particles with a particle size of less than 100 nm, and 1.0 wt% amino acids were added. The mixture was stirred at 250 r / min for 35 minutes, and the temperature of the mixed solution was controlled at 30℃ to obtain a mixed solution. The mixed solution was degassed and filtered, and then quantified by spinning. The pump metering fluid is ejected from the spinneret, and the fine filaments enter the coagulation bath for regeneration and molding to obtain fiber bundles. The fiber bundles undergo two-bath drawing, washing, desulfurization, washing, oiling, and winding to obtain antibacterial viscose fiber. The composition of the coagulation bath is: sulfuric acid 103 g / L, sodium sulfate 340.0 g / L, and zinc sulfate 9.0 g / L; the temperature of the coagulation bath is 46℃; the bath solution for the two-bath drawing is sulfuric acid 45.0 g / L, the temperature is 78℃, and the spinning speed is 35 m / min.

[0026] S2: Preparation of composite treated viscose fibers Dissolve 0.18 parts by weight of hydrolyzed polymaleic anhydride and 0.068 parts by weight of sodium hypophosphite in 60 parts by weight of deionized water, stir well, and adjust the pH to 4 with sodium bicarbonate to obtain the pretreated solution. Two parts by weight of antibacterial viscose fiber were completely immersed in the above pretreatment solution and soaked at room temperature (24°C) for 30 minutes to allow the pretreatment solution to fully penetrate. Then, the antibacterial viscose fiber was removed, squeezed with a rolling mill, and then pre-dried in an oven at 85°C for 5 minutes. The pre-dried fiber was then treated in an oven at 180°C for 4 minutes. The product was thoroughly washed three times with deionized water and finally dried at 50°C to constant weight to obtain the pretreated fiber. Mix 0.04 parts by weight of oleic acid with 0.02 parts by weight of Tween-80, and slowly add the mixture to 60 parts by weight of warm water at 50°C while stirring. Stir at 900 r / min for 10 min to obtain an oleic acid emulsion. 2.5 parts by weight of pretreated fiber were immersed in the above oleic acid emulsion and treated in a water bath at 50°C for 35 minutes. Then the pretreated fiber was taken out and washed three times with deionized water and dried at 50°C to constant weight to obtain composite treated viscose fiber.

[0027] S3: Preparation of epoxidized soybean oil-tea seed oil modified fiber Mix 5 parts by weight of epoxidized soybean oil and 8 parts by weight of tea seed oil at a speed of 300 r / min until homogeneous. Then add 3 parts by weight of Tween-80 and 2 parts by weight of OP-10, and stir at a speed of 300 r / min until fully dissolved to obtain the mixed oil. Under stirring at 1200 r / min, 30 parts by mass of deionized water were added dropwise to the mixed oil until a milky white uniform emulsion was formed. The mixture was then ultrasonically treated at 20W for 8 minutes to obtain a mixed emulsion. 0.4 parts by mass of the mixed emulsion were added to 60 parts by mass of deionized water, stirred evenly, and the pH was adjusted to 7 to obtain the mixed oil treatment solution. 2.5 parts by weight of composite-treated viscose fiber were completely immersed in the mixed oil treatment solution and treated in a 50°C water bath for 45 minutes. The composite-treated viscose fiber was then removed, extruded using a rolling mill, and the liquid content was controlled at 90%. It was pre-dried in an 80°C oven for 10 minutes, treated in a 120°C oven for 5 minutes, and finally washed three times with deionized water to remove unbound mixed oil treatment solution from the surface. Finally, it was dried at 60°C to constant weight to obtain epoxidized soybean oil-tea seed oil modified fiber.

[0028] S4: Preparation of mulberry silk elastic gneiss fabric Twisted mulberry silk was used as warp yarn, and epoxidized soybean oil-tea seed oil modified fiber was used as weft yarn. The warp density was 330 threads / 10cm and the weft density was 260 threads / 10cm. The fabric was woven into a four-warp gauze fabric using a rapier loom to obtain mulberry silk elastic gauze fabric.

[0029] Example 3: A method for preparing mulberry silk elastic gypsum fabric, such as Figure 1 As shown, it includes the following steps: S1: Preparation of antibacterial viscose fibers Wood pulp was soaked in a 19% sodium hydroxide solution with a pulp-to-solid ratio of 1g:10mL. The mixture was treated at 20°C for 1 hour, the sodium hydroxide solution was removed by pressing, and the product was then pulverized for 10 minutes until it was transformed into a loose flocculent body to obtain alkali cellulose. Alkali cellulose is placed in air with an oxygen concentration of 60% for 25 minutes to obtain aged cellulose; 11 parts by weight of aged cellulose and 5 parts by weight of carbon disulfide were mixed and reacted for 10 minutes to obtain cellulose carbamate. The cellulose carbamate was dissolved in a 4-6% sodium hydroxide solution with a material-to-liquid ratio of cellulose carbamate to sodium hydroxide solution of 1g:6mL to form a viscous spinning solution, which yielded viscose. The viscose was placed at 34°C for 22 hours for curing, while being filtered and degassed to obtain viscose fiber spinning solution.

[0030] 200 parts by weight of viscose fiber spinning solution, 20 parts by weight of nano-paspalum fiber, and 60 parts by weight of nano-silver colloidal aqueous solution were mixed. The nano-silver colloidal aqueous solution specifically contained 0.15 wt% nano-silver particles with a particle size of less than 100 nm, and 0.5 wt% amino acids were added. The mixture was stirred at 200 r / min for 40 minutes, and the temperature of the mixed solution was controlled at 30℃ to obtain a mixed solution. The mixed solution was degassed and filtered, and then passed through a spinning metering pump. The fiber is metered and ejected from the spinneret. The fine filaments enter the coagulation bath for regeneration and molding to obtain fiber bundles. The fiber bundles undergo two-bath drawing, washing, desulfurization, washing, oiling, and winding to obtain antibacterial viscose fiber. The composition of the coagulation bath is: sulfuric acid 105.0 g / L, sodium sulfate 330.0 g / L, and zinc sulfate 9.5 g / L; the temperature of the coagulation bath is 47℃; the bath solution for the second-bath drawing is sulfuric acid 55.0 g / L, the temperature is 80℃, and the spinning speed is 35 m / min.

[0031] S2: Preparation of composite treated viscose fibers Dissolve 0.16 parts by weight of hydrolyzed polymaleic anhydride and 0.07 parts by weight of sodium hypophosphite in 60 parts by weight of deionized water, stir well, and adjust the pH to 3 with sodium bicarbonate to obtain the pretreated solution. 2.3 parts by weight of antibacterial viscose fiber were completely immersed in the above pretreatment solution and soaked at room temperature of 23°C for 32 minutes to allow the pretreatment solution to fully penetrate. Then, the antibacterial viscose fiber was taken out, squeezed with a rolling mill, and then pre-dried in an oven at 90°C for 5 minutes. The pre-dried fiber was then treated in an oven at 185°C for 5 minutes. The product was thoroughly washed three times with deionized water and finally dried at 55°C to constant weight to obtain the pretreated fiber. Mix 0.05 parts by weight of oleic acid with 0.02 parts by weight of Tween-80, and slowly add the mixture to 60 parts by weight of warm water at 52°C while stirring. Stir at 850 r / min for 12 min to obtain an oleic acid emulsion. Two parts by weight of pretreated fiber were immersed in the above oleic acid emulsion and treated in a water bath at 52°C for 32 minutes. Then the pretreated fiber was removed and washed three times with deionized water and dried at 55°C to constant weight to obtain composite treated viscose fiber.

[0032] S3: Preparation of epoxidized soybean oil-tea seed oil modified fiber Mix 3 parts by weight of epoxidized soybean oil and 7 parts by weight of tea seed oil at a speed of 250 r / min until homogeneous. Then add 2 parts by weight of Tween-80 and 1 part by weight of OP-10, and stir at a speed of 250 r / min until fully dissolved to obtain the mixed oil. Under stirring at 2000 r / min, 25 parts by mass of deionized water were added dropwise to the mixed oil until a milky white uniform emulsion was formed. The mixture was then ultrasonically treated with a power of 20W for 10 minutes to obtain a mixed emulsion. 0.5 parts by mass of the mixed emulsion were added to 60 parts by mass of deionized water, stirred evenly, and the pH was adjusted to 6.5 to obtain the mixed oil treatment solution. Two parts by weight of composite-treated viscose fiber were completely immersed in the mixed oil treatment solution and treated in a 60°C water bath for 30 minutes. The composite-treated viscose fiber was then removed, extruded using a rolling mill, and the liquid content was controlled to be 100%. It was pre-dried in an 85°C oven for 8 minutes, treated in a 130°C oven for 4 minutes, and finally washed three times with deionized water to remove unbound mixed oil treatment solution from the surface. Finally, it was dried at 60°C to constant weight to obtain epoxidized soybean oil-tea seed oil modified fiber.

[0033] S4: Preparation of mulberry silk elastic gneiss fabric Twisted mulberry silk was used as warp yarn, and epoxidized soybean oil-tea seed oil modified fiber was used as weft yarn. The warp density was 330 threads / 10cm and the weft density was 260 threads / 10cm. The fabric was woven into a four-warp gauze fabric using a rapier loom to obtain mulberry silk elastic gauze fabric.

[0034] Comparative Example 1: Comparative Example 1 is a commercially available mulberry silk elastic fabric (a product sold by Zhangjiagang Baisijia Knitting and Textile Co., Ltd.).

[0035] Comparative Example 2: Compared with Example 1, Comparative Example 2 differs in that it does not use hydrolyzed polymaleic anhydride to treat antibacterial viscose fibers, but only uses oleic acid to treat antibacterial viscose fibers. The remaining steps are unchanged, and it is referred to as Comparative Example 2.

[0036] Comparative Example 3: Compared with Example 1, Comparative Example 3 differs in that it does not use oleic acid to treat antibacterial viscose fibers, but only uses hydrolyzed polymaleic anhydride to treat antibacterial viscose fibers. The remaining steps are unchanged, and it is referred to as Comparative Example 3.

[0037] Comparative Example 4: Compared with Example 1, Comparative Example 4 differs in that it first treats antibacterial viscose fibers with oleic acid, and then treats the pretreated fibers with hydrolyzed polymaleic anhydride. The remaining steps remain unchanged, and it is referred to as Comparative Example 4.

[0038] Comparative Example 5: Compared with Example 1, the difference of Comparative Example 5 is that epoxidized soybean oil is not added in step S3, but only 7 parts by weight of tea seed oil is used to modify the composite-treated viscose fiber. The other steps remain unchanged, and it is referred to as Comparative Example 5.

[0039] Comparative Example 6: Compared with Example 1, the difference of Comparative Example 6 is that tea seed oil is not added in step S3, but only 4 parts by weight of epoxidized soybean oil is used to modify the composite-treated viscose fiber. The other steps remain unchanged, and it is referred to as Comparative Example 6.

[0040] Comparative Example 7: Compared with Example 1, Comparative Example 7 differs in that nano-pastreak fibers are not added in step S1, while the other steps remain unchanged, and is referred to as Comparative Example 7.

[0041] Comparative Example 8: Compared with Example 1, Comparative Example 8 differs in that cellulose carbamate is not added in step S1, while the other steps remain unchanged, and is referred to as Comparative Example 8.

[0042] The elasticity of the mulberry silk elastic gauze fabrics prepared in Examples 1-3 and Comparative Examples 1-4 was tested using the method in GB / T3819-1997 "Textiles - Determination of Crease Recovery - Recovery Angle Method", and the results are shown in Table 1. The composite-treated viscose fibers prepared in Examples 1-3 and Comparative Examples 1-8 were tested for breaking strength using the methods in GB / T14337-2022 "Test Method for Tensile Properties of Chemical Fibers (Short Fibers)". The results are shown in Table 2. The mulberry silk elastic gauze fabrics prepared in Examples 1-3 and Comparative Example 5 were washed according to GB / T 8629-2017 "Home Washing and Drying Procedures for Textile Testing" using standard detergent in a type A washing machine. The program was set to gentle washing, and the number of washes was 0, 5, and 10. The antibacterial properties of the fabrics were recorded after different number of washes. The antibacterial properties were tested using the oscillation method in GB / T20944.3-2008 "Evaluation of Antibacterial Properties of Textiles". The results are shown in Table 3. The mulberry silk elastic gypsum fabrics prepared in Examples 1-3 and Comparative Examples 7-8 were tested for dynamic / static friction coefficients using the method in ASTM D3108-2001, "Standard Test Method for Coefficient of Friction Between Yarn and Solid Material". The results are shown in Table 4.

[0043] Table 1

[0044] Table 2

[0045] As shown in Table 1, the acute elastic recovery angle and the delayed elastic recovery angle of Examples 1-3 are superior to all comparative examples. The acute elastic recovery angle and the delayed elastic recovery angle of the commercially available fabric in Comparative Example 1 are 98.5° and 87.2°, respectively, indicating that the commercially available product mainly relies on spandex for elasticity, but the fabric's wrinkle recovery performance is limited. The acute elastic recovery angle and the delayed elastic recovery angle of Comparative Example 2 are 104.2° and 91.6°, respectively. This shows that although the surface lubrication of oleic acid reduces the coefficient of friction and improves the feel, the lack of internal cross-linking support from hydrolyzed maleic anhydride limits the improvement in elastic recovery. The acute elastic recovery angle and the delayed elastic recovery angle of Comparative Example 3 are 112.8° and 96.3°, respectively. The internal cross-linking network significantly improves the fiber's elastic recovery rate, but due to the lack of surface lubrication from oleic acid, the friction between fibers is still relatively high, affecting the overall crease recovery performance of the fabric. The examples employ a step-by-step treatment of internal cross-linking from hydrolyzed maleic anhydride and surface lubrication from oleic acid, resulting in a synergistic effect and improving the elastic recovery angle and elastic properties of the fabric. The acute elastic recovery angle and the mild elastic recovery angle of Comparative Example 4 were 107.6° and 92.8°, respectively. It can be seen that oleic acid treatment forms a lubricating film on the fiber surface, which can improve the elasticity of the fabric. However, without prior activation and enhancement by hydrolyzed polymaleic anhydride, oleic acid cannot fully adhere to the fiber surface, affecting the lubrication effect and thus limiting the improvement in elasticity.

[0046] As shown in Table 2, the breaking strength of Examples 1-3 is ≥3.22 cN / dtex, significantly better than the comparative examples. Comparative Example 2, treated only with oleic acid, has a breaking strength of only 2.61 cN / dtex, comparable to ordinary viscose fiber, indicating that oleic acid mainly plays a surface lubricating role and cannot improve the mechanical strength of the fiber itself. Comparative Example 3, treated only with hydrolyzed maleic anhydride, achieves a breaking strength of 3.09 cN / dtex, higher than Comparative Example 2, proving that the cross-linking enhancement of hydrolyzed maleic anhydride is the key step in improving strength. After cross-linking with hydrolyzed maleic anhydride, the fiber surface activity is enhanced, and the chemical bonding of oleic acid further optimizes the surface defects of the fiber, reducing stress concentration points and playing a reinforcing role. The breaking elongation of the examples is also better than that of Comparative Examples 2 and 3, indicating that the stepwise treatment with hydrolyzed maleic anhydride and oleic acid not only enhances the fiber strength but also improves the fiber flexibility, achieving a "strong but not brittle" modification effect. Comparative Example 4, which was first modified with oleic acid and then modified with hydrolyzed polymaleic anhydride, had a tensile strength of 2.84 cN / dtex, which was between that of Comparative Examples 2 and 3. This indicates that the oleic acid treatment first forms a lubricating film on the fiber surface, which hinders the subsequent penetration of hydrolyzed polymaleic anhydride into the fiber interior and affects the crosslinking effect. Therefore, the order of first modifying with hydrolyzed polymaleic anhydride for strengthening and then lubricating with oleic acid is necessary.

[0047] Table 3

[0048] As can be seen from Tables 2 and 3, the breaking strength and elongation at break of Examples 1-3 are higher than those of Comparative Example 5. After epoxidized soybean oil was not added, the breaking strength of Comparative Example 5 was only 2.56 cN / dtex. This is because epoxidized soybean oil can act as both a crosslinking reinforcing agent for fibers and a fixative for the active ingredients of tea seed oil. Through post-treatment, it can strengthen the structure of the formed viscose fiber, thereby improving the breaking strength. Furthermore, Examples 1-3 all showed an inhibition rate of ≥97.8% against Staphylococcus aureus and ≥96.5% against Escherichia coli. Comparative Example 5, which only included tea seed oil and did not contain epoxidized soybean oil, had an inhibition rate of only 68.4% (Staphylococcus aureus) and 72.7% (Escherichia coli). Although tea seed oil itself has antibacterial activity, it lacks the fixation effect of the cross-linked network of epoxidized soybean oil. Tea seed oil mainly adheres to the fiber surface through physical adsorption. After 5 and 10 washes, the inhibition rate of Examples remained above 90%, while the inhibition rate of Comparative Example 5 decreased to 38.5% and 34.2% after 10 washes. This shows that epoxidized soybean oil has a fixation effect on tea seed oil, which can keep the tea seed oil fixed on the fiber for a long time and continuously exert its antibacterial effect.

[0049] Table 4

[0050] As can be seen from Tables 2 and 4, the breaking strength and elongation at break of Examples 1-3 are higher than those of Comparative Examples 7-8. The breaking strength of Comparative Example 7 is 2.77 cN / dtex, and the breaking strength of Comparative Example 8 is 2.53 cN / dtex, with breaking elongations of 16.3% and 14.5%, respectively. It can be seen that the combination of nano-pastreak fiber and cellulose carbamate, through physical blending, constructs a synergistic network that possesses both rigidity and flexibility, thereby enhancing the physical function of antibacterial viscose fiber. The network structure formed by cellulose carbamate itself has the ability to improve physical strength. Therefore, the breaking strength of Comparative Example 8 decreased significantly after the addition of cellulose carbamate.

[0051] The static friction coefficients of Examples 1-3 were between 0.30 and 0.32, and the dynamic friction coefficients were between 0.21 and 0.23. The friction coefficient data maintained good consistency among the three examples. However, the static friction coefficients of Comparative Examples 7-8 were greater than 0.44, and the dynamic friction coefficients were greater than 0.32. It can be seen that the present invention uses nano-pachymanite fiber combined with cellulose carbamate to achieve precise control of the friction coefficient, avoiding the decrease in spinnability caused by fiber surface roughness. This allows the fiber to pass smoothly through each process in subsequent spinning and weaving while maintaining good fiber cohesion, thereby significantly improving spinning smoothness and spinning efficiency. The porous structure of nano-pachymanite fiber itself can transmit stress and control the friction coefficient. Therefore, the friction coefficient of Comparative Example 7, which does not contain nano-pachymanite fiber, increased the fastest. In contrast, the friction coefficient of Comparative Example 8, which does not contain cellulose carbamate, was also affected and increased because the nano-pachymanite fiber could not be well inserted.

[0052] It should be understood that those skilled in the art can make improvements or modifications based on the above description, and all such improvements and modifications should fall within the protection scope of the appended claims. Parts not described in detail in this specification are prior art known to those skilled in the art.

Claims

1. A method for preparing mulberry silk elastic gypsum fabric, characterized in that, Specifically, the following steps are included: S1: Preparation of antibacterial viscose fibers Viscose fiber spinning solution, nano-paleite fiber and nano-silver colloidal aqueous solution are mixed and stirred to obtain a mixture. The mixture is degassed and filtered, metered by a spinning metering pump and ejected through a spinneret. The spinneret enters a coagulation bath for regeneration and molding to obtain fiber bundles. The fiber bundles are then subjected to two-bath stretching, washing, desulfurization, oiling and winding to obtain antibacterial viscose fiber. S2: Preparation of composite treated viscose fibers Hydrolyzed polymaleic anhydride and sodium hypophosphite were dissolved in deionized water, stirred evenly, and the pH was adjusted to obtain a pretreatment solution. Antibacterial viscose fibers were completely immersed in the pretreatment solution to ensure full penetration. The antibacterial viscose fibers were then removed, extruded using a rolling mill, pre-dried, and then heat-treated, washed, and dried to constant weight to obtain pretreated fibers. Oleic acid and Tween-80 were mixed and slowly added to warm water with stirring to obtain an oleic acid emulsion. The pretreated fibers were immersed in the above oleic acid emulsion and treated in a water bath. Then the pretreated fibers were taken out, washed with deionized water, and dried to constant weight to obtain composite treated viscose fibers. S3: Preparation of epoxidized soybean oil-tea seed oil modified fiber Epoxidized soybean oil and camellia seed oil were mixed evenly, and then Tween-80 and OP-10 were added and stirred to obtain a mixed oil. Deionized water was added dropwise to the mixed oil while stirring until a milky white uniform emulsion was formed. The emulsion was then ultrasonically treated to obtain a mixed emulsion. The mixed emulsion was added to deionized water and stirred evenly to obtain a mixed oil treatment solution. The composite-treated viscose fiber was completely immersed in the mixed oil treatment solution and treated in a water bath. The composite-treated viscose fiber was then removed, extruded using a rolling mill, pre-dried and treated in an oven, and finally washed with deionized water and dried to constant weight to obtain epoxidized soybean oil-camellia seed oil modified fiber. S4: Preparation of mulberry silk elastic gneiss fabric Twisted mulberry silk was used as warp yarn, and epoxidized soybean oil-tea seed oil modified fiber was used as weft yarn. The warp density was 330 threads / 10cm and the weft density was 260 threads / 10cm. The fabric was woven into a four-warp gauze fabric using a rapier loom to obtain mulberry silk elastic gauze fabric.

2. The method for preparing mulberry silk elastic gypsum fabric according to claim 1, characterized in that, Step S1 involves preparing antibacterial viscose fibers, specifically including the following steps: 200-210 parts by weight of viscose fiber spinning solution, 20-25 parts by weight of nano-paflictrine fiber, and 60 parts by weight of nano-silver colloidal aqueous solution are mixed and stirred at 200-300 r / min for 30-40 minutes, controlling the temperature of the solution after mixing at 30℃ to obtain a mixture. The mixture is then degassed and filtered, and metered through a spinning metering pump and ejected through a spinneret. The spinneret enters a coagulation bath for regeneration and shaping to obtain fiber bundles. The fiber is drawn through a two-bath process, followed by washing, desulfurization, washing, oiling, and winding to obtain antibacterial viscose fiber. The coagulation bath consists of 102.0-105.0 g / L sulfuric acid, 330.0-360.0 g / L sodium sulfate, and 8.5-9.5 g / L zinc sulfate. The temperature of the coagulation bath is 46-48℃. The two-bath drawing bath consists of 45.0-65.0 g / L sulfuric acid at a temperature of 75-80℃ and a spinning speed of 35 m / min.

3. The method for preparing mulberry silk elastic gypsum fabric according to claim 2, characterized in that, Step S2 involves preparing composite-treated viscose fibers, specifically including the following steps: Dissolve 0.16-0.18 parts by weight of hydrolyzed polymaleic anhydride and 0.06-0.08 parts by weight of sodium hypophosphite in 60 parts by weight of deionized water, stir well, and adjust the pH to 3-4 with sodium bicarbonate to obtain the pretreated solution. Immerse 2-2.5 parts by weight of antibacterial viscose fiber completely in the above pretreatment solution and soak at room temperature (22-24℃) for 30-35 minutes to allow the pretreatment solution to fully penetrate. Then, remove the antibacterial viscose fiber, squeeze it with a rolling mill, and then pre-dry it in an oven at 80-90℃ for 5 minutes. Treat the pre-dried fiber in an oven at 180-190℃ for 3-5 minutes. Wash the product thoroughly with deionized water 3 times and finally dry it at 50-60℃ to constant weight to obtain the pretreated fiber. Mix 0.04-0.06 parts by weight of oleic acid with 0.02 parts by weight of Tween-80, and slowly add the mixture to 60 parts by weight of warm water at 50-55°C while stirring. Stir at 800-900 r / min for 10-15 min to obtain an oleic acid emulsion. Immerse 2-3 parts by weight of the pretreated fiber in the above oleic acid emulsion and treat it in a water bath at 50-55°C for 30-35 minutes. Then take out the pretreated fiber, wash it with deionized water 2-3 times, and dry it at 50-60°C to constant weight to obtain composite treated viscose fiber.

4. The method for preparing mulberry silk elastic gypsum fabric according to claim 3, characterized in that, Step S3 involves preparing the nanoemulsion, specifically including the following steps: Mix 3-5 parts by weight of epoxidized soybean oil and 7-8 parts by weight of tea seed oil at a speed of 200-300 r / min until homogeneous. Then add 2-3 parts by weight of Tween-80 and 1-2 parts by weight of OP-10, and stir at a speed of 200-300 r / min until fully dissolved to obtain the mixed oil. While stirring at 1200-2000 r / min, add 25-35 parts by weight of deionized water dropwise to the mixed oil until a milky white homogeneous emulsion is formed. Sonicate for 5-10 min to obtain the mixed emulsion. Add 0.4-0.6 parts by weight of the mixed emulsion to 60 parts by weight of deionized water, stir evenly, and adjust the pH to 6-7 to obtain the mixed oil treatment solution. Two to three parts by weight of composite-treated viscose fiber are completely immersed in the mixed oil treatment solution and treated in a water bath at 40-60℃ for 30-60 minutes. The composite-treated viscose fiber is then removed, extruded using a rolling mill, and the liquid content is controlled at 80-100%. It is then pre-dried in an oven at 80-90℃ for 5-10 minutes, treated in an oven at 120-150℃ for 3-5 minutes, and finally washed 2-3 times with deionized water to remove unbound mixed oil treatment solution from the surface. Finally, it is dried at 60℃ to constant weight to obtain epoxidized soybean oil-tea seed oil modified fiber.

5. The method for preparing mulberry silk elastic gypsum fabric according to claim 4, characterized in that, The preparation of the viscose fiber spinning solution in step S1 is as follows: Wood pulp is soaked in a sodium hydroxide solution with a concentration of 18-20% and treated at 18-25°C for 1-2 hours. The sodium hydroxide solution is then removed by pressing. The product is then pulverized for 5-10 minutes until it is transformed into a loose flocculent body to obtain alkali cellulose. Alkali cellulose is placed in air with an oxygen concentration of 60% for 20-30 minutes to obtain aged cellulose; 10-12 parts by weight of aged cellulose are mixed with 3-5 parts by weight of carbon disulfide and reacted for 5-10 minutes to obtain cellulose carbamate. The cellulose carbamate is dissolved in a 4-6% sodium hydroxide solution to form a viscous spinning solution to obtain viscose. The viscose is placed at 30-34℃ for 22-28 hours for curing, while being filtered and degassed to obtain viscose fiber spinning solution.

6. The method for preparing mulberry silk elastic gypsum fabric according to claim 5, characterized in that, The ratio of wood pulp to sodium hydroxide solution is 1g:(10-15)mL.

7. The method for preparing mulberry silk elastic gypsum fabric according to claim 5, characterized in that, The ratio of cellulose carbamate to sodium hydroxide solution is 1 g: (6-10) mL.

8. The method for preparing mulberry silk elastic gypsum fabric according to claim 2, characterized in that, The colloidal aqueous solution of nanosilver in step S1 specifically contains 0.1-0.15 wt% nanosilver particles with a particle size of less than 100 nm, and 0.5-2.0 wt% amino acids are added.

9. The method for preparing mulberry silk elastic gypsum fabric according to claim 4, characterized in that, The power of the ultrasonic treatment in step S3 is 20W.